Introduction of Procalcitonin Testing and Antibiotic Utilization for Acute Exacerbations of Chronic Obstructive Pulmonary Disease. (June 2019) - Ulrich, Robert J; McClung, Daniel; Wang, Bonnie R; Winters, Spencer; Flanders, Scott A; Rao, Krishna
Background: The majority of acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are triggered by nonbacterial causes, yet most patients receive antibiotics. Treatment guided by procalcitonin (PCT), a sensitive biomarker of bacterial infection, safely decreases antibiotic use in many controlled trials. We evaluated PCT implementation for inpatients with AECOPD at a large academic hospital. Methods: All patients admitted for AECOPD during the first 6 months of PCT-guided therapy were eligible for inclusion in this retrospective cohort study. Patients with PCT performed were compared with those without PCT. The primary outcome was antibiotic days of therapy (DOT). Secondary outcomes included 30-day readmission and mortality. Results: Of the 238 AECOPD admissions, 73 (31%) had PCT performed. Procalcitonin-tested patients were more likely to meet systemic inflammatory response syndrome (SIRS) criteria, require intensive care unit (ICU)-level care, and have a longer length of stay (LOS) compared with those without PCT. Even after adjustment for these factors, PCT-tested patients received more inpatient DOT and there was no difference in total DOT. However, a low PCT value (<0.25 ng/mL) was associated with a 25.5% ( P ⩽ .001) decrease in intravenous (IV) antibiotic DOT. Guideline-recommended follow-up testing was rare (12%). Procalcitonin measurement had no effect on 30-day readmission or mortality. Conclusions: In this real-world analysis of inpatients with AECOPD, PCT-guided therapy was poorly adopted by providers and was not associated with a decrease in total antibiotic DOT. However, a low PCT level was associated with a 25.5% decrease in IV antibiotic DOT, suggesting increased comfort stepping down from IV to PO therapy.